Current human T‐cell lymphotropic virus type 1 mother‐to‐child transmission prevention status in Kagoshima. Issue 4 (August 2014) - Nerome, Yasuhito; Kojyo, Kanami; Ninomiya, Yumiko; Ishikawa, Tamayo; Ogiso, Ayano; Takei, Syuji; Kawano, Yoshifumi; Douchi, Tsutomu; Takezaki, Toshiro; Owaki, Tetsuhiro
Abstract The aim of this study was to assess the current human T‐cell lymphotropic virus type 1 (HTLV‐I) mother‐to‐child transmission (MTCT) prevention system in Kagoshima Prefecture. We investigated the rate of carrier pregnant women from obstetrics facilities in Kagoshima by mail in 2012 and compared our results with previous study results. We interviewed carrier pregnant women about their choices for infant nutrition, and we interviewed midwives about the follow‐up system. In 2012, 8719 screening tests were performed, covering 58.1% of all pregnant women in Kagoshima; the rate of carrier pregnant women was 1.3%. Of 59 carriers, 39 chose short‐term breast‐feeding. The HTLV‐I carrier rate among pregnant women in Kagoshima has declined. The current HTLV‐I MTCT prevention system in Kagoshima is effective, but not sufficient. To bring the nutrition methods to completion, various types of support are needed. Further studies will elucidate many unsolved problems concerning MTCT.